APLIKASI SISTEM PENGOLAHAN DATA PENDUDUK (STUDI KASUS : DESA RANTAU MAKMUR): Data Rantau Makmur Village, MySQL, Population Data Processing, PHP, Information System. - -, Lisdarti (LP2M Universitas Nurdin Hamzah, 2019)
Rantau Makmur Village Office is a village government agency institution located in Rantau Makmur Village, Berbak District, Tanjung Jabung Timur Regency. Rantau Makmur Village Office serves the community in a variety of correspondence needs. One of them is Data Collection of the population and its processor in the form of monthly report and its application into the leges. But in the implementation there are still some problems. The problem is still often a mistake in processing or registering the population, This is because in processing still with manual process. Application of Information Systems Data Processing Population In Rantau Makmur Village Office was made with the aim to facilitate the Village Rantau Makmur to provide services more effective and efficient. This application is made with web programming language with MySQL database. The input of this information system is of population data, birth data, family head data, death data, moving data, migrant data. While the output of this information system is the report of population data, birth data, family head data, death data, data moved, and data of migrants. The results of this study are expected to assist employees in performing their duties properly.